Energy efficiency optimisation for heterogeneous cellular networks-based small cell power allocation. (26th November 2021) - Ziyu, Pan; Jie, Yang; Nan, Guo
During the study of wireless green communication, energy efficiency (EE) optimisation of heterogeneous cellular networks (HCNs) is always the hot topic. This paper studied the EE of HCNs in homogenous Poisson point process (HPPP) and proposed a new EE optimisation method based on small cell transmitting power allocation. First, it modelled the HCNs by using HPPP. Second, it derived the expression coverage probability and achievable rata in Rayleigh channel situations, and deduced the expression of EE in closed form. Finally, it optimised the small cell transmitting power via convex-optimum method in order to maximise EE for HCNs. The simulation results show that the small cell's transmitting power has significant effects on the HCNs' EE. Its essence is through reasonable setting of small cell's transmitting power to available help improve its efficiency.